Narcissism and self-enhancement: An underestimated relationship? - Moser, Klaus (Psihologia Resurselor Umane, 2024)
For decades, scholars have argued that self-enhancement and narcissism are closely related. However, more recently it has been argued that this relationship is overestimated. The current paper presents a conceptual analysis which, to the contrary, suggests that it is more probable that the relationship has been underestimated. It is proposed to differentiate between six versions of how self-enhancement can be related to narcissism: increase of classical self-enhancement, modesty refutation, defensive self-enhancement, denying self-enhancement, overshooting compensatory self-enhancement and suppressed compensatory self-enhancement. All six are consistent with the definition that self-enhancement represents a “tendentiously favorable view of oneself”. A combination of three parameters should be used to appropriately characterize which version of self-enhancement is related to narcissism in a setting, two correlations (between self-rating of an attribute and narcissism; between an objective measure of the attribute and narcissism) and one discrepancy measure (difference between self-rating and objective measure). Moreover, it is shown why a recently proposed data analytic strategy, the application of conditional regression analysis, leads to an underestimation of the relationship between narcissism and self-enhancement because it only captures two of these six versions. Finally, it is discussed how the distinction of versions of self-enhancement as related to narcissism could contribute to a better understanding of the effects of self-enhancement in narcissist